Fission Gas Behaviors and Relevant Phenomena in Different Nuclear Fuels: A Review of Models and Experiments - Guo, Jingyu; Lai, Huansheng; Zhou, Wenzhong; Wei, Jie (Frontiers in Energy Research, 2022)
Reactor structural integrity and nuclear safety are seriously affected by the fission gas behaviors and relevant physical phenomena in nuclear fuels. In this review, the fission gas behavior and relevant phenomena in different fuels for both models and experiments have been comprehensively overviewed, including fission gas release, gap/plenum pressure, grain growth, swelling, fission gas diffusion coefficients, fuel cladding mechanical and chemical interactions under irradiations. The fission gas behaviors can be classified into single fission gas behavior and combined fission gas behavior with more interacting physics together. Besides, fission gas behaviors are also profoundly influenced by fuel performance, which is different in different kinds of fuels. The data of different nuclear fuels are collected, for example, UO2, MOX, metallic, U3Si2, UN, UC, and TRISO fuels. The models and experiments on fission gas behaviors are summarized into figures and tables for better comparisons. The fission gas behaviors are mainly subjected to burnup, time, and temperature, which profoundly impact these behaviors. The burnup will motivate the fission gas release and other fission gas behaviors. With the fuel temperature increase, the extent of some fission gas behaviors will be more strengthened, including fission gas release, gap/plenum pressure, grain growth, swelling, fuel cladding mechanical and chemical interactions. The predicted data is consistent with the measured data, and the modeling results generally agree well with the experimental data. In addition, the observation of enhanced gas release at high burnups is unexpected. However, the modeling approaches on fission gas release behaviors still have certain uncertainties. Therefore, it still has considerable space to be improved and is worth studying in future work.